Anaerobic exercise affects the saliva antioxidant/oxidant balance in high-performance pentathlon attletes - de Lima Sant`Anna, M.; Casimiro-Lopes, G.; Boaventura, G.; Farinha Marques, A. T.; Meriwether Sorenson, M.; Simao, R.; Salerno Pinto, V. (Human Movement, 2016)
Purpose. Investigate free radical production and antioxidant buffering in military pentathletes` saliva after their performance of a standardized, running-based anaerobic sprint test (RAST). Methods. Seven members of the Brazilian Navy pentathlon team were recruited to perform a running-based anaerobic test (~90 sec). The participants provided samples of saliva before and after the test that were analyzed for biomarkers of oxidative stress such as lipid peroxidation, total antioxidant capacity and the quantity of two specific antioxidants, glutathione and uric acid. Results. The lipid peroxidation increased ~2 fold after RAST, despite an increase in total antioxidant capacity (46%). The concentration of reduced glutathione did not change, while the uric acid concentration increased by 65%. Conclusions. The evaluation in saliva following a sprint test that lasted no more than 90 sec was sensitive enough to reveal changes in redox state.